The influence pathways of residential environment on quality of life for migrants through social integration across different neighbourhoods: A case study of Yiwu, China / Liyan Huang - Liyan , Huang (2024)
In the past decades, the quality of life (QoL) in post-migration families has been one of the hottest research topics and has attracted considerable attention. The residential environment at the neighbourhood level is one of the most important factors affecting migrants’ QoL. However, most of the previous studies ignored the hierarchical nature of neighbourhood environments, and fewer studies addressed exploring the underlying pathways of the residential environment and the QoL of migrants. Moreover, mixed findings exist on the effectiveness of the residential environment in improving QoL. In response to calls for the increasing public health challenge of migrants living in the postmigration urban environment, this study adopts a combination of multilevel regression model, ordered logit model, bootstrap method of mediating effects, and semi-structured interview to explore the associations and influence pathways between the neighbourhoodlevel environment and QoL through social integration. Drawing on the quantitative and qualitative dataset with a case study of Yiwu, the study confirms the hierarchical nature of neighbourhood-level environments and reveals that neighbourhood effects can weaken the effect of housing conditions on subjective well-being. Neighbourhood facility accessibility, neighbourhood physical environment, and neighbourhood social environment have significant and positive associations with subjective well-being. Neighbourhood facility accessibility and neighbourhood safety positively correlate with mental health, and neighbourhood safety significantly predicts physical health. Moreover, migrants who live in the work-unit old neighbourhoods have significantly higher overall QoL and mental health than those who live in commercial housing neighbourhoods. Residential segregation leads to better mental health but lower subjective well-being among migrants. Additionally, the results reveal that the residential environment affects the QoL of migrants through four pathways: the enabling and sorting effect of economic integration, the protective effect of acculturation, the “social distance” effect of psychological integration, and the “localised social interaction” effect. Furthermore, the moderating effect of housing instability indicates that the negative effect of housing affordability on SWB is augmented for migrant groups with high housing instability and the positive effect of NFA on SWB is weakened for groups with high housing instability through economic integration. Hence, based on the triangulation of the quantitative results and qualitative findings, the conceptual framework was developed to indicate the influence pathways of the residential environment on the QoL of migrants across different neighbourhoods. These findings extend recent moves to recognize how the neighbourhood effects impact the QoL of migrants and add to the limited research on the hierarchy nature of neighbourhood environment on QoL. This study highlights that inclusive housing policies and socially mixed neighbourhoods are important for optimizing the health agenda for internal migrants in China and other developing countries with similar social contexts.